The effect of dry extract of Geranium Palustre herb on coagulation system = Вплив сухого екстракту трави герані болотної на систему зсідання крові - Ostapets, M. O.; Shevtsov, I. I.; Karabut, L. V.; Bereznyakova, M. E. (Journal of Education, Health and Sport, 2015)
Ostapets M. O., Shevtsov I. I., Karabut L. V., Bereznyakova M. E. The effect of dry extract of Geranium Palustre herb on coagulation system = Вплив сухого екстракту трави герані болотної на систему зсідання крові. Journal of Education, Health and Sport. 2015;5(8):119-125. ISSN 2391-8306. DOI 10.5281/zenodo.27484 http://dx.doi.org/10.5281/zenodo.27484 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A119-125 https://pbn.nauka.gov.pl/works/605723 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. UDC 615.322:582.751:615.273 THE EFFECT OF DRY EXTRACT OF GERANIUM PALUSTRE HERB ON COAGULATION SYSTEM ВПЛИВ СУХОГО ЕКСТРАКТУ ТРАВИ ГЕРАНІ БОЛОТНОЇ НА СИСТЕМУ ЗСІДАННЯ КРОВІ M. O. Ostapets, I. I. Shevtsov, L. V. Karabut, M. E. Bereznyakova М. О. Остапець, І. І. Шевцов, Л. В. Карабут, М. Є. Березнякова National University of Pharmacy, Kharkiv, Ukraine Національний фармацевтичний університет, Харків, Україна marina.ostapets.22@mail.ru Abstract The article is devoted to the studying of mechanism action on coagulation system the dry extract of Geranium Palustre herb. Established, those during 20-ty days of introduction the investigation extract increasing the activity of platelet’s mechanism of hemostasis (increasing platelet’s amount, their aggregation activity and retraction of blood clotting). On the background of introduction the investigation extract decreasing indicators of I and III phase of coagulation cascade (activated partial thromboplastin time, thrombin time), increasing prothrombin time and level of fibrinogen. Obtaining result suggest about active action the dry extract of Geranium Palustre herb on «external» way activation of hemocoagulation by possibility effect of accelerate the formation of thromboplastin, causing the hypercoagulation. The mechanism of antihemmorhagic action of dry extract of Geranium Palustre herb due to the presence in the composition biological active substances (such as tannins, flavonoids, elagic, galic and ascorbinic organic acids) that acting complex on vascular-platelet and coagulation hemostasis at the expense of increasing the strength and sealing vascular-tissue barriers, P-vitamin activity – it is ability to reduce capillary fragility and permeability and increasing their resistance. Key words: dry extract of Geranium Palustre herb, platelets, coagulation, phenolic compounds. Реферат Стаття присвячена дослідженню механізму дії сухого екстракту трави герані болотної на систему зсідання крові. Встановлено, що протягом 20-ти денного введення досліджуваного екстракту підвищувалася активність тромбоцитарної ланки гемостазу (підвищувалася кількість тромбоцитів, їх агрегаційна здатність та ретракція кров’яного згустку). На фоні введення сухого екстракту трави герані болотної знижувалися показники I та III фази коагуляційного гемостазу (активований частковий тромбопластиновий час, тромбіновий час), підвищувався протромбіновий час та рівень фібриногену. Отримані дані свідчать про вплив сухого екстракту трави герані болотної на «внутрішній» шлях активації зсідання крові за рахунок прискорення формування тромбопластину, що призводить до гіперкоагуляції. Механізм антигеморагічної дії сухого екстракту трави герані болотної обумовлений наявністю у складі біологічно активних речовин (дубильних речовин, флавоноїдів, елагової, галової та аскорбінової органічних кислот), які діють комплексно як на судинно-тромбоцитарний, так і на коагуляційний гемостаз за рахунок ущільнення та збільшення міцності судинно-тканинних бар’єрів, Р-вітамінної активності – здатності зменшувати проникність та ламкість капілярів, підвищувати їх резистентність. Ключові слова: сухий екстракт трави герані болотної, тромбоцити, зсідання крові, фенольні сполуки. Реферат ВЛИЯНИЕ СУХОГО ЭКСТРАКТА ТРАВЫ ГЕРАНИ БОЛОТНОЙ НА СИСТЕМУ СВЕРТЫВАНИЯ КРОВИ. Статья посвящена исследованию механизма действия сухого экстракта травы герани болотной на систему свертывания крови. Установлено, что на протяжении 20-ти дневного введения исследуемого экстракта повышалась активность тромбоцитарного звена гемостаза (увеличивалось количество тромбоцитов, их агрегационная способность и ретракция кровяного сгустка). На фоне введения сухого экстракта травы герани болотной снижались показатели I и III фазы коагуляционного гемостаза (активированное частичное тромбопластиновое время, тромбиновое время), повышалось протромбиновое время и уровень фибриногена. Полученные данные свидетельствуют о влиянии сухого экстракта травы герани болотной на «внутренний» путь активации свертывания крови за счет ускорения формирования тромбопластина, что приводит к гиперкоагуляции. Механизм антигеморрагического действия сухого экстракта травы герани болотной обусловлен наличием в составе биологически активных соединений (дубильных веществ, флавоноидов, эллаговой, галловой и аскорбиновой органических кислот), которые действуют комплексно как на сосудисто-тромбоцитарный, так и на коагуляционный гемостаз за счет уплотнения и увеличения прочности сосудисто-тканевых барьеров, Р-витаминной активности – способности уменьшать проницаемость и ломкость капилляров, повышать их резистентность. Ключевые слова: сухой экстракт травы герани болотной, тромбоциты, свертывание крови, фенольные соединения.